2003
DOI: 10.1161/01.cir.0000066691.52789.be
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Are Involved in Smoking-Induced Dysfunction of Nitric Oxide Biosynthesis and Upregulation of Endothelial Nitric Oxide Synthase

Abstract: Background-Our group has previously shown that human umbilical vein endothelial cells exposed to smokers' serum decreased nitric oxide (NO) production and endothelial nitric oxide synthase (eNOS) activity in the presence of increased eNOS expression. In the present study, we examined whether these observations extended to human coronary artery endothelial cells (HCAECs). In addition, the role of reactive oxygen species in the observed alterations was examined. Methods and Results-HCAECs were incubated with ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(97 citation statements)
references
References 28 publications
6
91
0
Order By: Relevance
“…After “validating” our model, we first sought to investigate the impact of e‐cigarettes on thrombogenesis, as it is the major cause of tobacco‐induced CVD,38 including thrombosis‐based diseases 17, 77, 78, 79, 80, 81, 82, 83. Our findings revealed, for the first time, a drastic reduction in the time for carotid artery occlusion, indicating a prothrombotic phenotype, even after only a week of whole‐body exposure to e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…After “validating” our model, we first sought to investigate the impact of e‐cigarettes on thrombogenesis, as it is the major cause of tobacco‐induced CVD,38 including thrombosis‐based diseases 17, 77, 78, 79, 80, 81, 82, 83. Our findings revealed, for the first time, a drastic reduction in the time for carotid artery occlusion, indicating a prothrombotic phenotype, even after only a week of whole‐body exposure to e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies have shown altered endothelial function by changes in nitric oxide biosynthesis when exposed to smoking and confirmed that oxidative stress has a central role in smoking-mediated dysfunction of nitric oxide biosynthesis in endothelial cells. 22 Alcohol intake, on the other hand, reduces glutathione production, causing increased levels of H 2 O 2 , which in turn reacts with transition metals in the mitochondria of the cells and contributes to oxidative stress. Glutathione in the mitochondria is the only protection available to metabolize H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Human endothelial cells exposed to sera from smokers have decreased nitric oxide availability despite increased nitric oxide synthase expression, with scavenging of nitric oxide by increased reactive oxygen species generation. 26,27 Smokingassociated endothelial dysfunction can be ameliorated by 3-hydroxy-3-methylglutaryl (HMG)-coenzyme A (CoA) reductase inhibitor therapy independently of changes in lipid levels, 28 by supplementation with tetrahydrobiopterin, 26 and by xanthine oxidase inhibition with allopurinol. 29 Monocytes isolated from smokers demonstrate increased adherence to endothelial cells, which is corrected by vitamin C therapy.…”
Section: Smoking-related Vascular Inflammation and Oxidative Stressmentioning
confidence: 99%